ICONIZATION OF SUFFERING IN THE ORIENTAL ARCH-NARRATIVE (IN A COMPARATIVE CONTEXT WITH WESTERN ARCH-NARRATIVES) - Plesník, Ľubomír (Porównania, 2019)
This thematologically oriented study is grounded in the Indian collection of tales Vetala Panchavimshati from the 11th century and its implicit comparison with European arch-narratives (especially traditional fairy tales). It seeks to identify similarities and differences in the portrayal of existential strategies that guarantee the most meaningful handling of Being (Dasein) in the iconized lifeworld, eo ipso in the fictional world. The goal of this comparative interpretation is the definition of two basic existential “arch-grammars”, which differ primarily in what the fictional world regards as a loss (deficit) and profit (surplus).